Predictors of maternal psychological distress among mothers of children with attention deficit hyperactivity disorder - Alexander, Charlotte Marie A/P Ambrose (2018)
Background: The American Psychiatric Association estimates a prevalence of four to six percent of the population of children to suffer from Attention Deficit Hyperactivity Disorder (ADHD). According to the National Institute of Public Health, a prevalence of 3.8% of Kelantan population of children suffer from disorders of hyperactivity. The difficult bidirectional interaction between parent and child create many conflicts. The occurrence of maternal stress, depressive and anxiety symptoms have been identified, with limited exploration of this reservoir of distress in the local population. Little is known about the role of social support among mothers of ADHD children. Objectives: This study aims to identify the presence of psychological distress among mothers of ADHD children, and to determine predictors of maternal psychological distress. Methods: This is a cross-sectional study that involved 100 mothers of ADHD children whose children attended outpatient child psychiatry clinic follow-up at Hospital Universiti Sains Malaysia, Kelantan, from 1st November 2016 until 30th June 2017. These children were clinically diagnosed to have ADHD according to the DSM-5 criteria and ranged between the ages of 2 to 18 years. All mothers who fulfilled selection criteria, and granted consent were provided with a socio-demographic and clinical information form, and two self-report questionnaires, namely Depression Anxiety and Stress Scale 21 and Multidimensional Scale of Perceived Social Support. A clinician-rated Children’s Global Assessment Scale was used to assess severity of ADHD.Results: A spectrum of maternal psychological distress was identified, whereby 53% of mothers reported depressive symptoms, 54% of mothers experienced anxiety symptoms and 39% of mothers reported stress symptoms. ADHD symptoms severity was significantly associated with all three psychological domains, with p<0.001 respectively. Similarly, perceived social support from family represented a significant predictor of overall maternal psychological distress, with p<0.001 in all three domains of depression, anxiety and stress. Other factors associated with depressive symptoms include race (p=0.036) and absence of other caretakers (p=0.006). Conclusion: This study identified overall maternal psychological distress among mothers of ADHD children in a local setting in Kelantan with depressive and anxiety symptoms recording the highest level. ADHD symptom severity, perceived social support from family, absence of other caretakers and race were identified as predictors of maternal psychological distress. This study suggests the need for psychological distress screening among mothers of ADHD children. More research should be garnered about the protective role of social support among these mothers.